Breath Tests to Assess Alcoholic Liver Disease - Furnari, Manuele; Ahmed, Iftikhar; J. van Erpecum, Karel; Savarino, Vincenzo; G. Giannini, Edoardo (Reviews on Recent Clinical Trials, 2016)
The prevalence of Alcohol related Liver Disease (ALD) continues to rise all over the world due to changing drinking behaviour of the population. Liver disease due to excessive alcohol consumption causes significant morbidity and mortality, and poses a substantial economic burden to the health care resources. Early diagnosis and treatment of ALD may help prevent progression to cirrhosis and hepatocellular carcinoma. The last decade has seen a rising interest in potential use of non-invasive tests in clinical practice, including diagnosis and monitoring of chronic liver diseases. Over the past few decades, breath testing has been investigated extensively in the diagnosis of ALD, and has shown promising results in predicting the early stages of ALD. A variety of breath tests have been utilised in this regard including the13Clabelled breath tests, aminopyrine breath test , galactose breath test , methacetin breath test, and keto-isocaproic acid breath test. These tests have demonstrated good results in identification of both significant and severe liver disease among patients with ALD. Volatile Organic Compounds (VOC) are chemicals, which can be quantified in breath and other biological fluids, and represent physio-pathological activities within an individual. Alteration in the pattern of breath VOCs can be correlated with a number of diseases including ALD. Early stages of ALD can be detected using these breath tests, which can lead to adoption of preventive measures to reduce the progression of liver disease. This review focuses on the clinical utility of current and future breath tests, including breath VOC, as a non-invasive means of predicting early stages of ALD.
Keywords: methacetin breath test